2018
DOI: 10.5513/jcea01/19.4.2366
|View full text |Cite
|
Sign up to set email alerts
|

Examining the racing performance and longevity in the Hungarian Thoroughbred population

Abstract: The aim of the study was to examine the factors affecting longevity (as the number of years spent in race) in the Hungarian Thoroughbred horse population, and to investigate the total earnings won during lifetime and per start. The performance data was collected from 3,029 Thoroughbred horses (1,704 female, 1,674 male) born between 1996 and 2018 in Hungary with full known racing career. A multivariate generalized linear model was used to estimate the effect of sex of the horses, age at first start and the mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…There was an inverse association between FRAM, raced races, and ACDM. Horses in this study that began their athletic careers at a younger age had longer careers and raced more times, concurring with the thoroughbred racehorse population in Australia, Hong Kong, New Zealand, Poland, Hungary, and Turkey (15,16,17,18,19,20) .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There was an inverse association between FRAM, raced races, and ACDM. Horses in this study that began their athletic careers at a younger age had longer careers and raced more times, concurring with the thoroughbred racehorse population in Australia, Hong Kong, New Zealand, Poland, Hungary, and Turkey (15,16,17,18,19,20) .…”
Section: Discussionsupporting
confidence: 74%
“…Research performed on racehorses in the UK (2) observed that 78% of fractures occurred during training, and at least 57% were stress fractures, demonstrating non-adaptation to the training regimen. Besides being a desirable feature in racing, scientific evidence suggests a positive influence of the early onset of controlled training, allowing the proper bone and cartilage adaptations to exercise (8,19,21) , resulting in longer athletic careers (22,23) . Regardless of what may be familiar to the TB horse industry, starting a racing career later in life may not diminish the rate of MS injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisa realizada em cavalos de corrida no Reino Unido (2) observou que 78% das fraturas ocorreram durante o treinamento, sendo pelo menos 57% fraturas por estresse, demonstrando a não adaptação ao regime de treinamento. Além de ser uma característica desejável nas corridas, as evidências científicas sugerem uma influência positiva do início precoce do treinamento controlado, permitindo as adequadas adaptações ósseas e cartilagíneas ao exercício (8,19,21) , resultando em carreiras atléticas mais longas (22,23) . Independentemente do que possa ser familiar para a indústria de cavalos PSI, iniciar uma carreira atlética mais tarde pode não diminuir a taxa de lesões do SME.…”
Section: Resultsunclassified